ActiveSchematics AutoRendering Mobile Device Optimization - Ferdinand Kusuma; Mieke van Vucht; Raymond de Vijlder (Institute of Research and Community Outreach - Petra Christian University, 2017)
In this modern era, technology is one of our main necessities. Technology is always evolving and changes from day by day. One of the major developments in technology is the increasing usage of mobile devices for personal use or even for company use. AA-AS/EDS-WIR2 is one of the sub departments in the Robert Bosch Company that creates applications for the automotive market. The department has created an application named ActiveSchematics AutoRendering. This application is used in car workshops to help mechanics to repair car defects by rendering the car schematics. This application is constructed with an ASP.NET framework combined with a standalone Delphi program as a plugin. The front-end development is done using HTML5, CSS, JavaScript code, and the back-end development is done using C#. The schematics are SVG-based with HTML as the container file. At present, the rendered schematics are not compatible when opened from a mobile browser, because the legacy support for interactivity (for example zooming and panning) is implemented without any mobile support code. The company wants the application to become a mobile device friendly application. The research proposal to be addressed is to solve which front-end libraries can be used to help the SVG schematics to implement mobile-based gesture compatibility. After some trial and error experiments, mobile device improvement will be implemented by adding jQuery, Hammer.js, jQuery PanZoom, and Bootstrap library. The experimental results have been successful and the company can have the mobile device friendly feature for their clients. This research shows that jQuery and hammer.js can be implemented on an SVG object to become a mobile device friendly schematic.